PENERAPAN LOGIKA FUZZY MAMDANI UNTUK MENENTUKAN DURASI PENYIRAMAN TANAMAN TOMAT - Nadya Almas; Erna Astuti (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The determination of tomato plant water requirements is influenced by changes in temperature, air humidity, and soil moisture content, which are constantly changing. This study uses the Mamdani Fuzzy Logic method to determine the duration of adaptive irrigation based on these three environmental parameters. The data used came from the Mendeley Data Repository with a total of 3,000 observations. The fuzzy system was designed with three input variables, one output variable, and 27 reasoning rules. The calculation process was performed using the scikit-fuzzy library in Google Colab. The results showed that the irrigation duration ranged from 2.05 to 19.99 minutes with an average of 9.60 minutes. The pattern of results shows a consistent response, namely that the watering duration increases when the temperature is hot and the soil is dry, and decreases when the humidity is high and the soil is wet. These findings prove that Mamdani Fuzzy Logic is effective as a computational approach to aid decision-making in smart irrigation systems for tomato plants.